Changes of the ratio of inl+ and inl- nuclei in heterocaryons of spontaneous revertant and by DNA-induced inl+ revertant Neurospora crassa strains - M. Schablik; A. Zsindely; J. Aradi; G. Szabo (Fungal Genetics Reports, 1977)
Changes of the ratio of inl+ and inl- in heterocaryons of spontaneous revertant and by DNA-induced inl+ revertant Neurospora strains